Hubungan antara pembangunan berkelanjutan dengan community based tourism: a systematic literature review - Miranda Rista Ilhami; Salahudin Salahudin (Universitas Merdeka Malang, 2021)
This study aims to examine more deeply the relationship between sustainable development and community based tourism. This study uses a systematic literature review method, articles taken from the publications of various publishers using the SCOPUS database and given restrictions on the year of publication from 2019 to 2021. The results of this study indicate that CBT is one of the most important approaches in realizing sustainable development. CBT has a very close relationship with sustainable development, where CBT is considered a very effective strategy for realizing sustainable development, because CBT focuses on local communities where local people play an active role as the owner of the resource as well as the main actor in the development of their natural resources. . So in this CBT concept, the community is empowered to develop their skills, culture, and natural potential without destroying it at all, because one of the indicators of the success of sustainable development is environmental preservation. The limitation in this study is that the researcher only focuses on the relationship between sustainable development and CBT and has not discussed the relationship between sustainable development and other indicators and in this study the researcher only used a limited number of previous studies, namely only 266 articles. So that the suggestion for future researchers who are interested in researching sustainable development is to study the relationship of sustainable development with other indicators and to use more previous research so that it can be generalized in a broader discussion.